PENGARUH MODEL ROLE PLAYING PADA MATERI PENERAPAN SILA-SILA PANCASILA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS III SEKOLAH DASAR - Puspa Putri, Sagung Manik; Dewa Bagus Sanjaya; I Nengah Suastika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
There is a big challenge in achieving ideal learning outcomes, where many students consider Pancasila material as a lesson full of memorization. Therefore, this study aims to identify the Effect of Role Playing Models on the Application of Pancasila Principles to Improve Learning Outcomes for Grade III Elementary School Students. This study uses a quantitative approach with a quasi-experimental method (quasi-experimental Research). The design applied is Posttest-Only Control Group Design. The population in this study were all elementary school teachers in Gugus 1 Panglima Sudirman, and the research sample was taken using a Simple random sampling technique consisting of an experimental group given treatment in the form of a Role Playing learning model involving simulations in Pancasila Education learning at SDN 19 Dauh Puri, while the control group used a conventional learning model at SDN 24 Dauh Puri. Before conducting hypothesis testing, posttest data from both groups first passed the analysis prerequisite test, namely the normality test, homogeneity test, and hypothesis testing using an independent sample t-test (Independent Sample T-Test). The results of the independent t-test hypothesis test obtained a significance value of 0.000 < 0.05, which means that there is an influence of the Role Playing model on the material of the Application of the Pancasila Principles on the Learning Outcomes of Grade III Elementary School Students. The conclusion is that there is an influence of the Role Playing model on the material of the Application of the Pancasila Principles on student learning outcomes.